El modelo de gestión administrativa y su incidencia en la rentabilidad de la cooperativa de ahorro y crédito san Antonio Ltda.”. del cantón Montalvo, Provincia de Los Ríos. - Garófalo Villena, Garófalo Villena (2014)
The low context the one which the cooperative system of Saving and Credit is developed, it is not known in its entirety, for this reason the necessity exists of studying this thematic one, by means of the investigation it is determined how its internal organisms work, the services that lend to their associates, are also looked for to identify the relationships between the cooperatives of Saving and Credit and their associates, to know if it is contributing with the society. This document presents contributions for the planning, organization and economic-financial control that it allows to develop the forms of making decisions, negotiating its resources that allow to guarantee its sostenibilidad - economic, social and environmental of the Cooperative of Saving and Credit "San Antonio Ltda." By means of the proposal he/she will obtain transparency in the use of the funds generating effectiveness and efficiency in the administration of the economic-financial resources, that which will contribute in the trust deposited in the organization by the different groups of interest, contributing to the stability and economic sostenibilidad of the cooperative, fulfilling their ends and social purposes...